Analisis Dampak Realokasi Anggaran Pendidikan dan Dinamika Ekosistem Pendidikan Nasioanl terhadap Sustainable Development Goals (SDGs) Indonseia - Febrian Nafisa Nurul Afida; Siti Maftuhah (Madrasah Ibtidaiyah Education Journal, 2026)
The dynamics of budget reallocation policies in Indonesia, which continue to evolve in response to economic pressures, national development priorities, and global crises, have the potential to affect the quality of educational services, equity of access, and the sustainability of the national education ecosystem. In the context of the Sustainable Development Goals (SDGs), particularly Goal 4 on quality education, it is essential to examine the extent to which such policies impact the achievement of sustainable development targets. This article aims to analyze the impact of education budget reallocation on the dynamics of the national education ecosystem and its implications for the achievement of SDGs in Indonesia. This study employs a qualitative approach with a descriptive-analytical research design, utilizing literature review and policy analysis of official government documents, education reports, and relevant secondary data. The findings indicate that education budget reallocation has a dual impact. On the one hand, it enhances efficiency and responsiveness to urgent needs. On the other hand, it potentially creates disparities in access and a decline in the quality of educational services, particularly in certain regions. Furthermore, the dynamics of the education ecosystem, shaped by technological factors, policies, and educational actors, play a crucial role in determining the success of SDG implementation in the education sector.